PREPARATION, OPTIMIZATION AND CHARACTERIZATION OF BIOCOMPATIBLE NANOALBUMIN-OFLOXACIN(BSANP-OF) CONJUGATE AND EVALUATION OF CONTROL RELEASE , ANTI BACTERIAL ACTIVITY AGAINST CLINICAL ISOLATE OF PSEUDOMONAS AERUGINOSA - Namasivayam, S.Karthick Raja; A.T.GEORGE ROBIN (Asian Journal of Pharmaceutical and Clinical Research, 2013)
ABSTRACT Objective. The objective of the present study is to synthesize and optimize bovine serum albumin nanoparticles coated with ofloxacin drug nano conjugate and evaluation of control release and anti bacterial activity against clinical isolate of Pseudomonas aeruginosa Methods.Simple coacervation technique was implemented for preparation of BSA nanoparticles and optimization was carried out with various parameters such as pH, Ethanol to BSA ratio and crosslinking time. The Nano-Drug conjugate was prepared using the optimized conditions along with ofloxacin. The Nanospheres thus formed were characterized by scanning electron microscopy and the control release, drug loading efficiency and entrapment efficiency was studied. Anti bacterial activity was studied with clinical isolate Pseudomonas aeruginosa adopting well diffusion assay. Results. The optimal pH was found to be 8.5 the ethanol to albumin ratio was fo be 5;1 and cross linking time of 8hrs which gives the higher yield of BSA nanoparticles.The Nanospheres thus formed were characterized using SEM which showed a particle size of nanosphere in the range of 160-230nm. The drug loading efficiency and entrapment efficiency was found to be 65 and 85% respectively. The in vitro drug release profiles show 81% release There was a controlled and a steady release of drugs from the nanoconjugate which showed distinct activity on Pseudomonas aeruginosa isolated from clinical samples. Conclusion. Nano albumin drug conjugate as an effective anti microbial agent against pathogenic bacteria would suggest the possible utilization of biocompatible non metallic nanoparticles –drug conjugate